Bis- and mono-substituted Chalcones exert anti-feedant and toxic effects on fall armyworm Spodoptera frugiperda - Priyanca Devi, Ahanthem (2021)
Spodoptera frugiperda is a highly polyphagous migratory lepidopteran pest species. It causes infestation in crops leading to the severe crop losses. Being a new invasive parasite, its susceptibility to insecticides needs to be explored; and therefore, there is an urgent need to develop the potent insecticides for the effective control of this insect pest. To attain the crop sustainability, the antifeedant, toxicity and nutritional effects on larvae of Spodoptera frugiperda were studied with six mono- and eight bis- substituted chalcones. The antifeedant activity was calculated when 50% of the larvae control ate 50% of the diet through the FR factor. Toxicity was assessed through larval, pupal mortality and the emergence of adults and nutritional effects with consumption rates (IC), growth (GR) and consumption efficiency (EIC). The bis-chalcones 6b, 6e, 6f and 6h caused lethal effect on S. frugiperda in the first larval stages, being 6b the most toxic (85%). Adults who survived showed malformations and decreased size, which led to death. The larvae fed with aggregate in the bis-chalcones diet: 6b, 6e and 6f had the highest percentage of intake and the poorest conversion of nutrient absorption (ECI), which suggests that the larva metabolizes food for energy and results in a decrease of growth and death in early stages. Bis-chalcones showed more toxicity than mono-chalcones and 6b causes the most toxic and dietary change.